Improved Intrinsic Activity of Ce0.5Pr0.5O2 for Soot Combustion by Vacuum/Freeze-Drying - Li, Qian; Su, Yimin; Liu, Xuesong; Lv, Yanan; Zhang, Nana; Xin, Ying; Zhang, Zhaoliang (Frontiers in Environmental Chemistry, 2021)
Vacuum-drying and freeze-drying were adopted to improve the catalytic activity of Ce0.5Pr0.5O2 for soot combustion. The specific surface area and pore volume of the as-prepared Ce0.5Pr0.5O2 were greatly increased compared to the counterpart using the common drying method. Furthermore, the redox performance and the oxidation ability for soot were enhanced, as demonstrated by H2-TPR and soot-TPR. Thus, lower combustion temperatures and higher intrinsic activity were obtained. This work demonstrated that simply changing the drying process of precipitates can be served as a paradigm to improve the structure and catalytic performance.